Study the effect of coumaron resin on chloroprene based rubber adhesive - سلامة غيث; حسن وسوف; براءة سيو (Latakia University Journal -Basic Sciences Series, 2022)
In this research, a chloroprene based rubber adhesive (contact adhesive) was prepared and the optimum ratio was studied to achieve the best compatibility between coumarone resin and chloroprene rubber (CR) in order to reach the best peel strength. Wherever, several percentages of coumarone resin were selected and the peel strength of a rubber/metal substrate was studied. The best percentage of achieving the highest peel strength of 4.2 N/mm was 25 Phr. It also gave a viscosity of 1164 C.P, which is the suitable viscosity for applying the adhesive by brushing method. Previous tests were carried out using a general mechanical testing device (FRANK) and viscosity device (BROOKFIELD).